Clinical profile of enteric fever: a prospective study of fifty enteric fever patients - Kakaria, Ashish; Asgaonkar, Dilip; Narkhede, Meenakshi (International Journal of Research in Medical Sciences, 2017)
Background: The protean manifestations of enteric fever make this disease a true diagnostic challenge. Untreated, typhoid fever is a grueling illness that may progress to delirium, obtundation, intestinal hemorrhage, bowel perforation, and death within 1 month of onset. Survivors may be left with long-term or permanent neuropsychiatric complications. This is a prospective study of fifty confirmed enteric fever adult patients done in Kasturba Hospital Mumbai. Methods: Fifty enteric fever patients with clinical and laboratory diagnosis were included in the study. They were admitted in wards with the aim of documenting the epidemiological pattern, clinical picture, therapeutic response and complications of Salmonella. Their history and detailed physical examination were recorded and tests including antibiotic sensitivity and resistance were done. Results: In the study incidence of fever 100%, chills 26%, vomiting 44%, diarrhea 28%, abdominal pain 64%, headache 26%, and signs as splenomegaly 36%, hepatomegaly 42%, rose spots 6%, relative bradycardia 34% were reported. Anemia, leukocytosis and leukopenia and elevated liver enzymes were found in 42.9%, 10%, 21% and 45% respectively. Incidence of Salmonella Typhi, Salmonella Paratyphi was 80% and 20% respectively. There was no mortality in the study. Conclusion: Clinical presentation, signs and symptoms of Typhoid fever patients are varying. For the confirmatory diagnosis in addition to a high index of suspicion, Widal test and blood culture are required. For the proper treatment of Typhoid fever in view of emergence of resistant strains of S. Typhi antibiotic sensitivity and resistance test should be done whenever facilities available.